Post-communist countries and their participation in international forums on energy [dataset] - Tosun, Jale; Mišić, Mile (Universität, 2021)
This dataset acompanies the paper "Post-communist countries and their participation in international forums on energy". This explorative analysis investigates in which international forums on energy Post-Communist countries participate and what motivates their participation. Theoretically, the article draws from theories of policy diffusion to explain why the Post-Communist countries have joined the 11 international forums on climate governance selected. It contends that the wish to follow the example of high-status countries or organizations, considerations concerning economic competitiveness, and the wish to obtain access to knowledge are potential factors explaining membership. Empirically, the article uses explorative methods to probe the plausibility of the three hypotheses. The database comprises information on the participation of 28 Post-Communist countries in 11 pertinent international forums, which are all characterized by a low degree of formalization and voluntary cooperation. Our findings show that neither the European Union nor Russia as a high-status organization or country had a robust impact on the Post-Communist countries’ decision to join the international forums on energy of interest. Instead, our indicative and preliminary findings suggest that access to knowledge was the most relevant driver of participation.